The earliest low and high δ18O caldera-forming eruptions of the Yellowstone plume: implications for the 30–40 Ma Oregon calderas and speculations on plume-triggered delaminations - Seligman, Angela N.; Bindeman, Ilya N.; McClaughry, Jason; Stern, Richard A.; Fisher, Chris (Frontiers in Earth Science, 2014)
We present new isotopic and trace element data for four eruptive centers in Oregon: Wildcat Mountain (40 Ma), Crooked River (32–28 Ma), Tower Mountain (32 Ma), and Mohawk River (32 Ma). The first three calderas are located too far east to be sourced through renewed subduction of the Farallon slab following accretion of the Yellowstone-produced Siletzia terrane at ~50 Ma. Basalts of the three eastern eruptive centers yield high Nb/Yb and Th/Yb ratios, indicating an enriched sublithospheric mantle source, while Mohawk River yields trace element and isotopic (δ18O and εHf) values that correlate with its location above a subduction zone. The voluminous rhyolitic tuffs and lavas of Crooked River (41 x 27 km) have δ18Ozircon values that include seven low δ18Ozircon units (1.8–4.5 ‰), one high δ18Ozircon unit (7.4–8.8 ‰), and two units with heterogeneous zircons (2.0–9.0 ‰), similar to younger Yellowstone-Snake River Plain rhyolites. In order to produce these low δ18O values, a large heat source, widespread hydrothermal circulation, and repeated remelting are all required. In contrast, Wildcat Mountain and Tower Mountain rocks yield high δ18Ozircon values (6.4–7.9 ‰) and normal to low εHfi values (5.2–12.6), indicating crustal melting of high-δ18O supracrustal rocks. We propose that these calderas were produced by the first appearance of the Yellowstone plume east of the Cascadia subduction zone, which is supported by plate reconstructions that put the Yellowstone plume under Crooked River at 32–28 Ma. Given the eastern location of these calderas along the suture of the accreted Siletzia terrane and North America, we suggest that the Yellowstone hotspot is directly responsible for magmatism at Crooked River, and for plume-assisted delamination of portions of the edge of the Blue Mountains that produced the Tower Mountain magmas, while the older Wildcat Mountain magmas are related to suture zone instabilities that were created following accretion of the Siletzia terrane.